Reflections on The Dimensions of Trust among online Consumers: A Review - Raju, Mary Metilda; Kanusamy, Malathi (Journal of Contemporary Research in Management (JCRM), 2017)
Â Abstract Online shopping is fast growing today due to the rapid proliferation of the Internet. It is reported that only a small minority of website visitors (about 1%) returns to make purchases (Gupta & Kim, 2007). Buyers have limited information and cognitive resources available, and thus seek to reduce the uncertainty and complexity of online transactions by applying mental shortcuts. One effective mental shortcut is trust, which can serve as a mechanism to reduce the complexity of human conduct in situations where people have to cope with uncertainty. Because of limited control over the seller and the absence of proven guarantees that the seller will not engage in undesirable opportunistic behaviors, trust is a critical aspect of online shopping. Indeed, some researchers have suggested that buyers generally have stronger intentions to transact with online sellers whom they trust. A characteristic like trust is a major factor reflecting on the online shopping environment, where buyers are unable to personally scrutinize the seller, physically examine the merchandise, or collect the merchandise upon payment. Hence, this paper is a research review related to the contribution of the factor â€˜trustâ€™ on the online shopping behavior.